ANALISIS PENGARUH KOMPENSASI, FASILITAS, LINGKUNGAN KERJA, BEBAN KERJA DAN KEPEMIMPINAN TERHADAP EMPLOYEE ENGAGEMENT MENGGUNAKAN SPSS - Muttakin, Mumtaz; Putra, Sabar Hanadwi; Subekti, Zaenal Mutaqin (Jurnal informasi dan komputer, 2023)
This study is based on the writer's curiosity, "why there are employees who can survive and work until retirement and why there are new employees join and then resign in a short term?", Then the analysis of the curious followed by studied previous studies to be a reference in this study.The objective of this study is to determine whether the compensation, facilities, work environment, workload and leadership affect to Employee Engagement in the Company. This study is a quantitative descriptive research, the data obtained from the sample of population , then analyzed with the statistical methods and interpreted. The hypothesis test used 98 respondents who gave back the questionnaire for sample from 130 populations. The analytical technique used multiple linear regression with SPSS, and the research results said that there is significant effect of compensation (65%), facilities (68.1%), work environment (53.2%), work load (75%) and leadership (62.7%) partially, and simultaneously affecting 77.8% to Employee Engagement of the Company. The Company is expect to maintain Employee Engagement stability by paying attention to compensation, facilities, work environment, workload, and leadership that becomes the determinant variable of employee engage or not.